Social equity and public administration: Origins, developments, and application - Frederickson, H. George (New York : Routledge, 2010)
Designed to be the definitive statement on social equity theory and practice in public administration .
Social equity and the new public administration -- Social equity in context -- Social equity : the democratic context and the compound theory -- Social equity and the question of administrative discretion -- The state of social equity in American public administration -- An intergenerational social equity ethic -- Social equity, law, and research -- When education quality speaks, education equality answers -- Social equity in the twenty-first century : in memory of Philip J. Rutledge.
Includes bibliographical references and index.
Keywords: PUBLIC ADMINISTRATION; PUBLIC WELFARE--MANAGEMENT